KEDISIPLINAN DAN TUNJANGAN KINERJA DAPATKAH MEMPENGARUHI MOTIVASI KERJA PEGAWAI SEKRETARIAT DAERAH KOTA BANDA ACEH ? - Meutia Handayani (JURNAL EKOMBIS, 2020)
The purpose of this study was to determine the effect of discipline and performance allowances on employee working motivation at the Regional Secretariat of Banda Aceh City. This study used quantitative research methods, and data were analysed by using multiple linear regression analysis. Tools analysis used by SPSS 25version. The primary data were collected through questionnaires to public official at The Regional Secretariat of Banda Aceh City. The statistical method used the classical assumption test, the partial t test and the simultaneous F test. The results showed that partially test discipline had no effect on employee working motivation, but performance allowances had effect on employee working motivation. Simultaneous test concluded that both discipline and performance allowances had an effect on employee working motivation at the regional secretariat of Banda Aceh City.Keywords: Discipline, Performance Allowances, Employee Working Motivation